2017
DOI: 10.1530/erp-17-0002
|View full text |Cite
|
Sign up to set email alerts
|

Clinical events and echocardiographic lesion progression rate in subjects with mild or moderate aortic regurgitation

Abstract: BackgroundThe rate of progression of aortic regurgitation (AR) is not well described. Current guidelines state that asymptomatic patients with mild AR should be followed up every 3–5 years and 1–2 yearly for moderate AR. This study describes the lesion and clinical based progression of mild and moderate AR in a population of patients undergoing systematic follow-up.Methods and results341 patients with either mild or moderate AR were included. The rates of clinical events (death, aortic valve replacement and ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
2
5
0
Order By: Relevance
“…Valvular involvement in RHD children in this current study was predominately mitral regurge (88.6%) and this is consistent with other local and worldwide studies El-Aroussy et al 19 , Elamrousy et al 20 and Ghamrawy et al 21 in Egypt and by Lubega et al 22 in Uganda and Badiani et al 23 By using multivariate Logistic regression analysis, the current study reported that RHD was 2.6 more times among urban children. These results go with finding of Riaz et al 24 and Ghamrawy et al 21 Many Egyptian villages have shown rapid urbanization, resulting in congested socioeconomically depressed localities.…”
Section: Discussionsupporting
confidence: 91%
“…Valvular involvement in RHD children in this current study was predominately mitral regurge (88.6%) and this is consistent with other local and worldwide studies El-Aroussy et al 19 , Elamrousy et al 20 and Ghamrawy et al 21 in Egypt and by Lubega et al 22 in Uganda and Badiani et al 23 By using multivariate Logistic regression analysis, the current study reported that RHD was 2.6 more times among urban children. These results go with finding of Riaz et al 24 and Ghamrawy et al 21 Many Egyptian villages have shown rapid urbanization, resulting in congested socioeconomically depressed localities.…”
Section: Discussionsupporting
confidence: 91%
“…However, the RHD control program in El-Mahalla succeeded in the early detection of cases of RHD before severe valvular involvement has occurred. Consistent with other local [31,34] and worldwide [26,35,60,61] studies, the majority of the RHD cases had mild mitral regurgitation. Trivial valvular effects were recorded for 241 (11.3%) patients who were counselled regarding the appropriate duration of secondary prophylaxis and advised to attend regular follow-up visits to prevent progressive damage to their valves.…”
Section: Clinical Presentation and Cardiac Sequelaesupporting
confidence: 88%
“…Mild to moderate AR is in general not regarded as a major clinical problem in patients with normal LVEF 15,16 despite its high prevalence in the age groups > 70 years. 2,3 HF is also highly prevalent in the elder age groups, 4 making coincidental occurrence of HF with AR likely.…”
Section: Prevalence Of Aortic Regurgitation and Chronic Heart Failurementioning
confidence: 99%